2019
DOI: 10.1155/2019/8010356
|View full text |Cite
|
Sign up to set email alerts
|

High Bone Mineral Density of the Lumbar Spine Is Positively Associated with Breast Cancer

Abstract: Objective. The objective of this study was to verify possible associations between bone mineral density (BMD) and breast cancer in recently diagnosed women in the Brazilian Mid-west region, considering the menopausal status of patients. Methods. A case-control study was conducted with 142 cases of breast cancer and 234 controls matched by for age, body mass index (BMI), and menopausal status (pre- and postmenopause), performed in a university hospital in the Brazilian Mid-west. Lumbar spine (L1–L4), femoral ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…However, the random effects of the model showed that women who reported breast cancer during follow-up visits had higher BMD at baseline than women who remained free of breast cancer. This is consistent with other research findings associating high BMD with the risk of breast cancer [1][2][3][4]. Furthermore, women who reported breast cancer lost BMD at a faster rate throughout the follow-up periods, eventually descending to lower BMD levels than those of women free of breast cancer.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the random effects of the model showed that women who reported breast cancer during follow-up visits had higher BMD at baseline than women who remained free of breast cancer. This is consistent with other research findings associating high BMD with the risk of breast cancer [1][2][3][4]. Furthermore, women who reported breast cancer lost BMD at a faster rate throughout the follow-up periods, eventually descending to lower BMD levels than those of women free of breast cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Also in 2013, a retrospective study of Israeli women found an association between breast cancer and higher BMD in the lumbar spine, femoral neck, and total hip [3]. A more recent case-control study in 2019 confirmed that breast cancer in Brazilian women was associated with high BMD in the lumbar spine, but not in the femoral neck or total femur [4]. Interestingly, a 2022 case-control study reported that BMD in women with breast cancer was higher compared with those in a control group, even though the breast cancer cases had lower average vitamin D levels, which are normally associated with bone health [1].…”
Section: Introductionmentioning
confidence: 98%
“…In several observational studies, women newly diagnosed with breast cancer, prior to any antitumor therapy, have been found to have higher BMD than women without breast cancer, and BMD is positively correlated with the incidence of breast cancer. High BMD is considered a biomarker of breast cancer risk [38][39][40] . However, bone mineral density was not found to be a risk factor for breast cancer in ourr MR Study.…”
Section: Discussionmentioning
confidence: 99%
“…For the growth and maturation of bone estrogen is considered to be an important factor and in adults, it also helps in the regulation of bone turnover [70]. Estrogen exerts a protective effect on bone as estrogen receptors are found on osteoblasts and osteoclasts; thus the tissue of bone is responsive to estrogen [71].…”
Section: Effect Of Estrogen On Skeletal Integrity: Molecular Mechanismmentioning
confidence: 99%